Pelayanan E-Court di Pengadilan Agama Trenggalek - Erin Farida Rohma; Farah Nur Fitria; Indana Zulfa; Fitrotul Ula; Hoirotus Syahriyah; Ittaqi Tafuzi; Kristanti Putri Eka Wardani; Moh. Ilyas; Hafid Qurrahman; M. Firdaus Setiawan; Mohamad Ajib; Ninuk Kusrini; Mariatul Qibtiyah; Miftahul Jannah; Nanda Maulandari; Nasihatul Farihah; Sufyan Assauri; Nikmatul Maula; Fahrur Ulum; Shobirin . (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
Abstract: This article discusses e-court services at the Trenggalek Religious Court. This research is a qualitative research. Data collection was carried out through observation and literature study. The collected data were analyzed descriptively. The Trenggalek Religious Court is a state institution which is also one of the religious courts that proclaims the realization of an increase in modern justice services. The Trenggalek Religious Court launched the WBK (Corruption Free Area) and WBBM (Clean and Serving Bureaucratic Areas) programs. To achieve this, religious courts provide good quality services to the community by launching a service work pattern for justice seekers through PTSP (One Stop Services) and e-court. The Trenggalek Religious Court has implemented an e-court service where the plaintiffs and applicants and advocates can file cases in online form, which regulates from users of case administration services, case administration registration, summons of parties, issuance of copies of decisions, and administrative governance. Payment of case fees which are entirely made electronically/ online when submitting an application / lawsuit for civil, religious, state administration cases that apply in each judicial environment. In this regard, religious courts should always innovate and improve services, so that they are in accordance with the principles of simple, fast and low cost justice. Keywords: Service, E-court, Trenggalek Religious Court. Abstrak: Artikel ini membahas tentang pelayanan e-court di Pengadilan Agama Trenggalek. Penelitian ini adalah penelitian kualitatif. Pengumpulan data dilakukan melalui observasi dan studi pustaka. Data yang terkumpul dianalisis secara deskriptif. Pengadilan Agama Trenggalek merupakan lembaga negara yang juga termasuk salah satu pengadilan agama yang mencanangkan terwujudnya peningkatan pelayanan hukum yang berkeadilan yang modern. Pengadilan Agama Trenggalek mencanangkan program WBK (Wilayah Bebas Korupsi) dan WBBM (Wilayah Birokrasi Bersih dan Melayani). Untuk mewujudkan itu, pengadilan agama memberikan kualitas pelayanan kepada masyarakat yang baik dengan mencanangkan pola kerja pelayanan terhadap para pencari keadilan melalui PTSP (Pelayanan Terpadu Satu Pintu) dan e-court. Pengadilan Agama Trenggalek sudah menerapkan pelayanan e-court dimana para pihak penggugat dan pemohon serta advokat dapat mengajukan perkara dalam bentuk online, yang mengatur mulai dari pengguna layanan administrasi perkara, pendaftaran administrasi perkara, pemanggilan para pihak, penerbitan salinan putusan, dan tata kelola administrasi, pembayaran biaya perkara yang seluruhnya dilakukan secara elektronik/online saat mengajukan permohonan/gugatan perkara perdata, agama, tata usaha negara yang berlaku di masing-masing lingkungan peradilan. Berkaitan dengan hal tersebut, hendaknya pengadilan agama selalu berinovasi dan memperbaiki pelayanan, agar sesuai dengan asas peradilan sederhana, cepat dan biaya ringan. Kata Kunci: Pelayanan, E-court, Pengadilan Agama Trenggalek.